Development of single station lightning detection system - Mohd Azrin, Mohd Arif Fadzillah (2012)
The lightning strikes billion of times, kill many of people, and damages billion of assets per year. This problem may be properly managed by using a lightning detection system. In this project, the lightning detector circuit was designed by using PIC16F877A microcontroller. The purposes of this project are to determine the distance and direction of lightning strikes. One wire antenna and apair of loop antenna were attached to the circuit. A pair of loop antennas is used to sense the magnetic field produce by the lightning strike and a wire antenna is used to sense the electric field produce by the lightning strike. Three variable resistor will act as the antenna in this project to give the variety input to the PIC microcontroller. CCS compiler is a software used to write the program to microcontroller. The program written for Graphic User Interface (GUI) is done by using Microsoft Visual Basic 6.0. LED will blink and LCD will display the data of distance and direction of lightning strike. Meanwhile, GUI will display the results also with the add on of electric field and magnetic field values of each antenna and saveall the data in a laptop.